Critical Care Approach to Severe Tetanus with Septic Shock: A Case Report - Veva Wulandari; Aswoco Andyk Asmoro (HM Publisher, 2025)
Introduction: Tetanus, caused by Clostridium tetani neurotoxin, remains a life-threatening condition, particularly in regions with suboptimal vaccination coverage. Severe tetanus often necessitates intensive care unit (ICU) admission due to profound muscle spasms, respiratory failure, and autonomic nervous system dysfunction. Concomitant septic shock further complicates management and worsens prognosis. This report details the critical care management of a patient presenting with severe tetanus complicated by septic shock. Case presentation: A 41-year-old male presented with generalized muscle rigidity, trismus, and recurrent severe spasms following a puncture wound from bamboo 10 days prior. He had no prior tetanus immunization history. Upon admission, he exhibited signs of respiratory distress (Sp90% on a 15L non-rebreather mask) and septic shock (tachycardia, hypotension requiring vasopressors, SOFA score 7). Diagnosis of severe tetanus (Ablett Grade III) with respiratory failure and septic shock was made. Management involved immediate intubation, mechanical ventilation, administration of human tetanus immunoglobulin (HTIG), intravenous metronidazole, aggressive sedation with benzodiazepines (diazepam infusion) and neuromuscular blockade (vecuronium infusion), hemodynamic support with intravenous fluids and noradrenaline infusion, early tracheostomy, and comprehensive supportive care including nutritional support and VTE prophylaxis. His ICU stay was complicated by autonomic instability and ventilator-associated pneumonia (VAP). Conclusion: Managing severe tetanus complicated by septic shock requires a prompt, multidisciplinary critical care approach. Key elements include securing the airway, controlling spasms and rigidity, neutralizing toxins, eradicating the source, managing autonomic instability, aggressive sepsis management according to current guidelines, and providing meticulous supportive care. Despite significant challenges, a favorable outcome is possible with comprehensive ICU management.